Nitrogen and sulfur co-doped graphene composite electrode with high electrocatalytic activity for vanadium redox flow battery application. (1st December 2020) - Li, Qiang; Bai, Anyu; Xue, Zhichao; Zheng, Yang; Sun, Hong
Abstract: Nitrogen and sulfur co-doped graphene has been decorated on graphite felt electrode via a hydrothermal treatment using thiourea as sulfur and nitrogen sources for vanadium redox flow battery application. Our results demonstrate that the modification of sulfur and nitrogen co-doped graphene on graphite felt provides an effective way to improve surface area and introduce functional groups for vanadium redox reaction, resulting in a significant improvement in energy efficiency (85.37% at a current density of 80 mA/cm 2 ), power density (0.4925 W/cm 2 ), discharge capacity and capacity retention. These results reveal that the modification of nitrogen and sulfur co-doped graphene on graphite felts is a promising method for the enhancement of vanadium redox flow battery performance.